A critical assessment of the calculation and analysis of thermodynamic parameters from adsorption data - Banera, Mauro Jonathan (2015)
Proper analysis of thermodynamic parameters obtained from adsorption data is a basic requirement for the characterization and optimization of an adsorption-dependent process like the action of organic corrosion inhibitors. Thus, this work aims at presenting a critical assessment of typical flawed examples from the literature together with alternative good practice to be considered, for preference.